Degenerated Subserosal Uterine Leiomyoma Mimicking Carcinoma Ovary - Ranabhat, Bijay Kumar; Dangal, Ganesh (Journal of Nepal Health Research Council, 2024)
Uterine leiomyomas are the most common entities encountered in routine gynaecological practice. They are usually easily identifiable on routine imaging. However, there is increasing difficulty with diagnosing leiomyoma following hyaline degeneration as it might mimic ovarian pathology. A stepwise and a multidisciplinary approach in management of these cases is preferred to achieve optimal results. We report a case of 40-year-old female presented to outpatient department with radiological diagnosis of complex adnexal mass and Ca-125 value 122 U/ml. Physical examination and radiological investigations suggested giant abdominopelvic mass, probably aggressive uterine or ovarian tumor preoperatively. Postoperative findings revealed hyaline degeneration of fibroid arising from anterior wall of uterus. Keywords: Degeneration; ovarian tumor; uterine leiomyoma.